TEACHER’S WAY TO FOSTER CRITICAL THINKING IN THE CLASSROOM (A Case Study of a Senior High School in Bandung) - Ni Putu Ayu Nopta Apsari (Journal of English and Education, 2016)
This study describes the way teacher fosters critical thinking in the classroom when teaching argumentative essay at Senior High School level. It aims to understand and describe the way teacher fosters critical thinking in the classroom when teaching argumentative genre at the Senior High School level. A qualitative case study was employed as a research design in this study. The data were collected through several instruments namely observation and interview which were then analysed using the theory of critical thinking approach by Ennis (1992 as in Emilia, 2005), teaching stages suggested by Emilia (2005) and the critical thinking cues instruction suggested by Paul Elder (2007) and Bloom (1956). The result of the study revealed that approach used by the teacher to foster critical thinking in students is infusion approach. Furthermore, the teacher only provides three of four teaching stages suggested by Emilia (2005). The teacher had infused critical thinking in the classroom mainly through question-answer process or from her instruction when teaching argumentative essay. The teacher only provide three categories of Paul Elder’s (2007) critical instruction and four categories of Bloom’s (1956) critical cues.